Driving Structural Equation Modeling (SEM) Growth Innovation and Digital Capabilities - Bramantyo, Sandy; Wahyu Eko Pujianto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In today’s dynamic business environment, small and medium enterprises (SMEs) face increasing challenges that threaten their performance and sustainability. Specific Background: Business owners are compelled to adapt by leveraging innovation and digital transformation, yet the mechanisms linking these elements remain underexplored. Knowledge Gap: Previous studies have not sufficiently examined how digital capabilities mediate the relationship between innovation capability and entrepreneurial performance. Aims: This study aims to investigate the effect of innovation capability and entrepreneurial orientation on entrepreneurial performance, while assessing the mediating role of digital capability. Results: Using purposive sampling, data were collected from 205 SME stakeholders in Sidoarjo and Pasuruan, including shop heads, managers, and supervisors. Analysis with SmartPLS 4.0 revealed that both innovation capability and entrepreneurial orientation significantly enhance entrepreneurial performance. Furthermore, digital capability was found to significantly mediate the positive relationship between innovation capability and performance. Novelty: This research introduces a moderated mediation model that highlights the strat egic importance of digital competence in strengthening innovation-led performance among SMEs. Implications: The findings provide practical insights for SMEs to prioritize innovation and digital development, enabling them to remain competitive in an increasingly digital economy. Highlights: Highlights the mediating role of digital competence in SME innovation. Demonstrates positive impact of innovation and orientation on performance. Uses SmartPLS 4.0 to validate structural relationships in the model. Keywords: Innovation Capability, Entrepreneurial Orientation, Digital Capability, Entrepreneurial Performance